The Effects of ATO on Mitochondria Apoptosis Pathway Genes Expression in APL Cell Line - Maede Sharifizadeh; Kimia Davarian; Mehrdad Hashemi; Majid Momeni; Kamran Ali Moghdam; Ardeshir Ghavamzadeh; Hamidollah Ghafari; Abolfazl Movafagh (Asian Pacific Journal of Cancer Biology, 2016)
Purpose and Background: Acute promyelocystic leukemia is the most malignant acute leukemia that leads to death in few weeks. It constitutes 10-15% of acute myelocystic leukemia. Arsenic trioxide, as a single agent factor, is known as the best treatment for acute promyelocystic leukemia, which mainly functions by inducing apoptosis. However, there is no clear image of the mechanism through which apoptosis is induced and how the genes expression is deeply affected. Thus, the present study is an attempt to examine the effect of the agent on expression of the genes dealing with the cancer. Methodology: The study was carried out as an analytical work. To find out about the mechanisms effective on inducing apoptosis, cell line NB4 were cultured with 0.5µM, 1 µM, and 2 µM arsenic trioxide and their RNA was extracted after 12hrs, 24hrs, 28hrs, and 72hrs. Following cDNA synthesis, apoptosis genes expression at mitochondria pathway including caspase 3, Mcl-1, and Bcl-2 were examined using Real-Time PCR. The data was analyzed using t-test and variance analysis in Excel. Findings: It was found that arsenic caused apoptosis was featured with decrease of mRNA expression of Bcl-2 anti-apoptotic. However, expression of caspase 3 and Mcl-1 genes remained unchanged after culturing by arsenic. Conclusion: The results showed that changes in Bcl-2 gene expression can be considered as a mechanism of apoptosis caused by arsenic, while caspase 3 and Mcl-1 genes had no effect on the mechanism.